Work Discipline of Civil Servants in The Regional Secretariat of Cirebon Regency - Himmah, Rojwa Al Himmah; Sitorus, Prandika; Nariyah, Hery (Journal of Comprehensive Science, 2025)
Work discipline is an important element in supporting the professionalism of civil servants, but its implementation in local government environments still faces structural and cultural challenges. This study aims to understand how work discipline is implemented and interpreted by civil servants in the Regional Secretariat of Cirebon Regency. Using a descriptive qualitative approach, data was obtained through semi-structured interviews, observation, and documentation. Data validity was strengthened through method triangulation and source triangulation, by exploring perspectives from various categories of informants. Analysis was conducted based on seven dimensions of discipline according to Singodimedjo's theory, which include compensation, leadership example, clarity of rules, enforcement of sanctions, supervision, leadership attention, and work habits. The research findings indicate that the implementation of discipline still depends on individual awareness and leadership character, while reward systems, rule enforcement, and supervision have not been consistently implemented. A strong discipline culture has not yet been established because leadership attention and routines are not yet grounded in a sustainable system. These findings emphasize the importance of discipline development based on values, social relationships, and organizational habits as part of local-level bureaucratic reform.